Quality of Electronic TB Register Data Compared with Paper-Based Records in the Kyrgyz Republic - Daniil Shauer; Ofelya Petrosyan; Manik Gemilyan; Edward M. Kamau; Pruthu Thekkur; Olga Goncharova; Kalmambetova Gulmira; Bolot Kyrbashov; Kylychbek Istamov; Meder Kadyrov; Ewan Wilkinson (Tropical Medicine and Infectious Disease, 2023)
This study evaluated the effectiveness of an electronic system for managing individuals with drug-sensitive pulmonary tuberculosis in the Kyrgyz Republic. This cohort study used programmatic data. The study included people registered on the paper-based system in 2019 and 302 people registered on both the electronic and the paper-based systems between June 2021 and May 2022. The data from the 302 individuals were used to assess the completeness of each form of record and the concordance of the electronic record with the paper-based system. This study showed that for most variables, the completeness and concordance were 85.3–93.0% and were lowest for nonmandatory fields such as medication side effects (26.8% vs. 13.6%). No significant difference was observed in the time taken from symptom onset to diagnosis and treatment initiation between the two systems. However, the electronic system had a significantly higher percentage of subjects who initiated treatment on the day of diagnosis (80.3% vs. 57.1%). The proportion with successful outcomes was similar in both groups, but the electronic system had a significantly lower proportion of individuals with outcomes that were not evaluated or recorded (4.8% vs. 14.3%, p < 0.001). This study highlights the potential advantages and gaps associated with implementing an electronic TB register system for improving records.